Thermal testing of the light pipe prototype - Omishore, Ayodeji (Array, 2019)
A light pipe prototype with a concentrating mirror parabolic head was tested for temperature profiles. The purpose of the testing was to find maximal temperature and estimate potential problems for overheating in the position of the pipe installation into roof structures. Infrared thermography monitoring of the light pipe prototype and temperature measurements give overview about the light pipe system temperature distribution. It was proven that the light pipe head temperature was increased for more than 100°C in thermally insulated structure under intensive infrared radiation.